(untitled) (Journal of the College of Basic Education, 2022)
Sport is a growing recreational activity, and as a result of the importance of sport, the designers tended towards the construction of sports buildings, especially stadiums, as they have become basic components in the urban fabric that makes up cities, in addition to achieving the focus of ambition, as it is considered one of the most “visible” types of buildings in history thanks to the Olympic Games and international sporting events. the other